2015
DOI: 10.1182/blood-2015-02-628800
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis links NFATC2 with asparaginase hypersensitivity

Abstract: Key Points The rs6021191 variant in NFATC2 is associated with an increased risk of asparaginase hypersensitivity and is an expression quantitative trait locus associated with expression of NFATC2. Exome interrogation confirms the importance of the HLA-DRB1*07:01 allele in asparaginase hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 36 publications
3
73
0
2
Order By: Relevance
“…human leukocyte antigen HLA-DRB1). [15,16] It can be anticipated that the combination of the two pathways can explain a larger portion of the risk for asparaginase allergy, but further studies are needed to confirm this hypothesis. Another well-studied example in the HLA region is carbamazepine-induced hypersensitivity reactions which are linked to the HLA-B*15:02 and HLA-A*31:01 haplotypes.…”
Section: Current Perspective On Pediatric Pharmacogenomicsmentioning
confidence: 99%
See 2 more Smart Citations
“…human leukocyte antigen HLA-DRB1). [15,16] It can be anticipated that the combination of the two pathways can explain a larger portion of the risk for asparaginase allergy, but further studies are needed to confirm this hypothesis. Another well-studied example in the HLA region is carbamazepine-induced hypersensitivity reactions which are linked to the HLA-B*15:02 and HLA-A*31:01 haplotypes.…”
Section: Current Perspective On Pediatric Pharmacogenomicsmentioning
confidence: 99%
“…[13,14] Another example of the childhood ALL pharmacogenomics, currently at the discovery level, is the allergic reaction in response to therapy with asparaginase. [15,16] Hypersensitivity to asparaginase can lead to dose reduction, suboptimal drug exposure, and subsequent treatment failure. [15,16] Pharmacogenomics studies identified genetic variants affecting the expression of the asparagine synthetase (ASNS) gene and variants in the genes that regulate the immune responses (i.e.…”
Section: Current Perspective On Pediatric Pharmacogenomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only 10 pharmacogenetics studies analyzing L-ASP have been performed in pediatric ALL [34,[41][42][43][44][45][46][47][48][49]. Among them, six specifically focused on the analysis of the risk to L-ASP hypersensitivity, finding the most remarkable results with 15 polymorphisms located at GRIA1, HLA-DRB1, NFATC2 and ASNS (Table 1) [34,[41][42][43][44]49].…”
Section: Pharmacogeneticsmentioning
confidence: 99%
“…Among them, six specifically focused on the analysis of the risk to L-ASP hypersensitivity, finding the most remarkable results with 15 polymorphisms located at GRIA1, HLA-DRB1, NFATC2 and ASNS (Table 1) [34,[41][42][43][44]49]. Interestingly, out of these 15 significant polymorphisms, 11 were located in the GRIA1 gene (glutamate receptor, ionotropic, AMPA 1).…”
Section: Pharmacogeneticsmentioning
confidence: 99%